2001
DOI: 10.1182/blood.v97.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Raised blast glutathione levels are associated with an increased risk of relapse in childhood acute lymphocytic leukemia

Abstract: A preliminary study has linked raised blast glutathione levels with chemoresistance in acute myeloid and lymphoblastic leukemia in adults and children. In this study, therefore, the relationship between leukemic blast glutathione levels and prognosis in childhood acute lymphoblastic leukemia (ALL) was investigated. A total of 77 childhood ALL samples were analyzed, 62 at initial presentation and 15 at relapse. A 20-fold interindividual variation in glutathione levels at presentation (median, 6.54 nmol/mg prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…This finding supports the results of previous studies concerning various type of tumours (Goasguen et al, 1996;Buser et al, 1997;Howells et al, 1998;Kearns et al, 2001). For example, Buser et al (1997), in a series of 89 women with untreated breast cancer, found that high levels of Gst and Gpx activities were associated with favourable clinical characteristics and a good prognosis, whereas low levels of Gst activity were associated with more aggressive or more advanced disease, although the results did not reach the limit of statistical significance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding supports the results of previous studies concerning various type of tumours (Goasguen et al, 1996;Buser et al, 1997;Howells et al, 1998;Kearns et al, 2001). For example, Buser et al (1997), in a series of 89 women with untreated breast cancer, found that high levels of Gst and Gpx activities were associated with favourable clinical characteristics and a good prognosis, whereas low levels of Gst activity were associated with more aggressive or more advanced disease, although the results did not reach the limit of statistical significance.…”
Section: Discussionsupporting
confidence: 83%
“…As GSTP1 is the major GSTs consistently expressed in both normal and tumour breast tissue (Forester, Carcinogenesis 1990;11: 2163-2170, it can be hypothesised that low GSTP1 expression would reduce the global activity of GSTs, and consequently reduce glutathione (GSH) consumption in GSTcatalysed reactions, thereby leading to higher levels of GSH, which would block apoptosis and promote proliferation of tumour cells. This hypothesis was first proposed by Kearns et al (2001), who reported an association between elevated GSH levels in leukaemia cells and an increased risk of relapse in childhood acute lymphoid leukaemia. Morales et al (2005) recently confirmed these results, by showing that intracellular glutathione levels determine cell sensitivity to drug-induced apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…26,27 This concept is supported by data from a recent report in which high intracellular GSH levels in lymphoid blasts were correlated with greater risk of relapse and reduced overall survival in childhood ALL. 21 Interestingly, in the same study there was no relationship between glutathione levels and in vitro drug sensitivity. 21 The prognostic importance of the GST genotype was supported by our multivariate analysis, where the GST genotype was an independent predictor for overall survival.…”
Section: Discussionmentioning
confidence: 87%
“…21 Interestingly, in the same study there was no relationship between glutathione levels and in vitro drug sensitivity. 21 The prognostic importance of the GST genotype was supported by our multivariate analysis, where the GST genotype was an independent predictor for overall survival. In particular, GST genotyping could discriminate between favorable and unfavorable prognosis in the cytogenetically defined intermediate-risk group, which contains the majority of AML patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation